2022
DOI: 10.1111/dmcn.15303
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback assisted relaxation training and distraction therapy for pain in children undergoing botulinum neurotoxin A injections: A crossover randomized controlled trial

Abstract: Aim To compare biofeedback assisted relaxation training (BART) with distraction therapy for pain during botulinum neurotoxin A (BoNT‐A) treatment. Method This was a crossover randomized controlled trial. Eligible participants were 7 years and older with neurological conditions. Participants were randomized to receive BART or distraction during their first BoNT‐A treatment, followed by the alternative intervention in their subsequent BoNT‐A treatment. BART was delivered via BrightHearts, an interactive heart‐ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Strategies like positive reinforcement, behavioral modeling, guided imagery or hypnoanalgesia, and muscle relaxation and/or breathing exercises before and after the procedure are appropriate [ 6 ]. Other strategies, such as virtual reality, biofeedback-assisted relaxation training, and the presence of Child Life specialists in the room, have been studied and have shown increasing effectiveness in pain control during procedures [ 18 , 20 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategies like positive reinforcement, behavioral modeling, guided imagery or hypnoanalgesia, and muscle relaxation and/or breathing exercises before and after the procedure are appropriate [ 6 ]. Other strategies, such as virtual reality, biofeedback-assisted relaxation training, and the presence of Child Life specialists in the room, have been studied and have shown increasing effectiveness in pain control during procedures [ 18 , 20 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was possible to extrapolate data for analysis and comparison among 19 out of the 23 articles obtained (Table 2). Ostojic [18] 2022 RCT The sample sizes were very different among the studies, with variability ranging from n=10 to n=758 and an average sample size of 120 children with a mean age of 8.36 years old (min. 3.79; max.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A systematic review examining the efficacy of interventions in children and adolescents with CP (57 studies) found many studies were low-moderate quality [ 10 ]. There is moderate-high evidence to support intrathecal baclofen therapy for pain secondary to hypertonia in spastic and spastic-dyskinetic CP, non-pharmacological interventions (including distraction and biofeedback) for procedural pain, and pharmacological interventions for postoperative pain [ 10 , 61 ]. Low-quality evidence exists for deep brain stimulation to reduce pain severity, frequency, and analgesia requirement in children with severe dystonic CP [ 62 ].…”
Section: Management Of Pain In Children and Young People With Cpmentioning
confidence: 99%
“…Pain during and after procedures is common; however, there is a slow uptake of the application of evidence-based, non-pharmacological management in this setting. Research indicates a role for distraction, imagery, and preparation/education for children and young people with CP [ 10 , 61 ].…”
Section: Management Of Pain In Children and Young People With Cpmentioning
confidence: 99%
“…Some institutions that have not implemented nitrous gas for all their patients yet have been exploring treatment alternatives and the study by Ostojic et al is timely in exploring whether topical anesthesia plus either distraction or biofeedback‐assisted relaxation training (BART) might be an alternative to nitrous gas 2 . While the authors did not mention the level of overall pain, worst pain, and fear in their cohort of 38 children mostly with cerebral palsy, the data seem to suggest that neither integrative modality was an effective alternative to nitrous gas.…”
mentioning
confidence: 99%